Efficacy and safety of multiple external therapies in patients with insomnia: a systematic review and network meta-analysis - Wang, Zhen; Xu, Hui; Wang, Zheng; Zhou, Hang; Zhang, Lijuan; Wang, Yu; Li, Miaoxiu; Zhou, Yunfeng (Frontiers in Neurology, 2024)
Background The annual incidence of insomnia continues to increase owing to changes in lifestyle habits, increased work pressure, and increased environmental pollution. In recent years, an increasing number of external therapies have been proven effective in treating insomnia and have been widely used. However, the relative benefits and harms of external therapies remain uncertain, and an optimal treatment strategy has not yet been determined. Objectives A network meta-analysis was performed to evaluate and compare the efficacy and safety of multiple external therapies for patients with insomnia. Methods Eight electronic databases were comprehensively searched from their inception to June 2023 for relevant literature. We also searched the grey literature and reviewed the reference lists of related systematic reviews. Two independent reviewers performed the study selection, data extraction, and bias assessment of the included randomized controlled trials (RCTs) using the Cochrane Reviewers’ Handbook, and a network meta-analysis was conducted using Stata and RevMan software. Results In total, 14,826 studies were identified. Of these, 83 studies, including 9 external therapies and 6,100 patients, were deemed eligible for the present network meta-analysis. Except for the SL outcome, each external therapy was better than conventional medicine and the sham intervention (SI) in improving sleep quality. In terms of improving the psychological state indices of insomnia patients, each external therapy was superior to the SI; each external therapy had a better effect on the regulation of monoamine neurotransmitters. Tuina may be the most effective intervention in improving the total effective rate, Pittsburgh sleep quality index score, and SL. Repetitive transcranial magnetic stimulation (rTMS) perhaps resulted in the best improvement in total sleep time and awakening time (surface under the cumulative ranking curve [SUCRA] = 78.3 and 75.4%, respectively); and moxibustion (MB) and hyperbaric oxygen (HBO) were the most effective in reducing Self-rating Anxiety Scale and Self-rating Depression Scale scores. In terms of improving the monoamine neurotransmitters 5-hydroxytryptamine, norepinephrine, and dopamine, the best interventions were acupoint catgut embedding, electroacupuncture, and Tuina (SUCRA = 82.0, 69.9 and 90.3%, respectively). Safety results showed that the three safest interventions were the SI, Tuina, and foot bath. No serious adverse events were reported across the studies, and the most common minor adverse events included drowsiness, pain, excessive thirst, and hematoma. Conclusion Both Tuina and rTMS have significant effects on improving sleep quality, but the safety of rTMS is low. Therefore, Tuina can be recommended as the first line of treatment to improve sleep quality. If a patient’s anxiety and depression symptoms are evident, MB or HBO can be selected for treatment based on the actual situation. External therapy to improve sleep quality may be related to the regulation of monoamine neurotransmitters, which may be a potential mechanism of action. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=440882.